Teologia Politica Ed Ecclesiologia «Del Piccolo Numero»: L'idea Del Martirio Nel Giansenismo Italiano Settecentesco - Rochini, Marco (Rivista di storia del cristianesimo, 2018)
Considering the most relevant works of some noteworthy authors, this article aims at reconstructing the thought of the eighteenth century Italian Jansenism concerning the theme of martyrdom. During the eighteenth century some of the most important followers of Jansenism, such as Pietro Tamburini, Giuseppe Zola, Giovanni Battista Guadagnini, Giuseppe Maria Pujati, Scipione de Ricci, reflected more or less systematically on the theme of martyrdom. This article develops an analysis of the ecclesiology and the political theology of the eighteenth century Italian Jansenism. This perspective of research makes it possible to highlight how the reflection of Jansenism regarding the theme of martyrdom had mainly rhetorical and propaganda purposes, aimed at criticizing the authority of the Roman curia and the pope. The analysis of the thought of Italian Jansenism about martyrdom constitutes a privileged point of view for understanding the evolution of the identity and self-perception of this religious movement during the eighteenth century.